Professional’s perception in the management of the clinical waste in the ambulatory care centers in a municipality in the Metropolitan Region of Sorocaba, SP, Brazil - de Camargo, Ândrea Regina; Barra Nova de Melo, Ismail (O Mundo da Saúde, 2017)
In 2004, the Brazilian Health Regulatory Agency (ANVISA - National Health Surveillance Agency), published Resolution 306 of the Collegiate Board of Directors (RDC), which established the criteria for clinical waste disposal (RSS) management, by informing the kind of waste and their segregation, packaging, storage, transport and destination. The goal of this investigation is to determine the professional’s perception in the management of clinical waste in the ambulatory care centers in a municipality of the Metropolitan Region of Sorocaba, SP, Brazil. Method: individual qualitative interviews were used to collect data. As seen in the results, most of the professionals do not have the technical knowledge required for managing RSS. In addition, they indicated a lack of training in this area, which limits the involvement of health professionals with environmental matters. It was also evident that health professionals place the procedures directly associated with patient care as their priority, putting aside crucial matters connected to the development of preventative practices related to environmental preservation and the promotion of the population’s quality of life.